2018
DOI: 10.18502/kss.v3i10.3362
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Control Systems, Open Innovation and Sustainable Competitive Advantage

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In a broader analysis, the objective is to accelerate internal innovation and expand markets for the external use of innovation, influencing organizational results. In this sense, and according to [69], for the organizations of the different regions to pursue the principles of open innovation, the key element is to discover: what the organization lacks, what can be achieved internally and what can be integrated from the outside. Thus, unlike the traditional model of vertical integration, open innovation leads us to seek external sources of ideas, in addition to internal flows of knowledge, to increase the innovation process [68].…”
Section: The Role Of Innovation In the Performance Of European Union Regions And Its Interactions With Open Innovationmentioning
confidence: 99%
“…In a broader analysis, the objective is to accelerate internal innovation and expand markets for the external use of innovation, influencing organizational results. In this sense, and according to [69], for the organizations of the different regions to pursue the principles of open innovation, the key element is to discover: what the organization lacks, what can be achieved internally and what can be integrated from the outside. Thus, unlike the traditional model of vertical integration, open innovation leads us to seek external sources of ideas, in addition to internal flows of knowledge, to increase the innovation process [68].…”
Section: The Role Of Innovation In the Performance Of European Union Regions And Its Interactions With Open Innovationmentioning
confidence: 99%
“…Knowledge management capacity as a dynamic capability, reconfiguring and realigning knowledge capacity refers to an organization's ability to successfully manage its knowledge base over time. The concept can be considered as an open innovation framework, as a complement to absorption capacity and a step towards understanding dynamic capabilities to manage knowledge so that create competitive advantages (Rajagukguk, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Chenhall and Moers [62] revealed that the design of management control systems has developed in response to organisations' need to address the challenges of operating in uncertain settings by embracing innovation. Rajagukguk [63] pointed out that management accounting and control systems are a useful framework to link technical decisions to economic outcomes and convert innovation potential into economic value.…”
Section: Discussion: the Abc And Open Innovationmentioning
confidence: 99%
“…Through a broader analysis, the objective is to accelerate internal innovation and expand markets for the external use of innovation, influencing organisational results, 'open innovation needed to combine internal research with external ideas and then deploy those ideas both within their systems and also through other companies' systems. The key for these firms is to figure out what necessary missing pieces should be internally supplied and how to integrate both internal and external pieces into systems and architectures' [63] (p. 81).…”
Section: Discussion: the Abc And Open Innovationmentioning
confidence: 99%
See 1 more Smart Citation